Infrastructures within the student teaching practicum that nurture elements of lesson study - Elipane, Levi Esteban (Animo Repository, 2012)
A single case of student teaching program in a Fuzoku school in Japan was highlighted in the hope of elevating certain ruminations on how the essential features of Lesson Study are legitimized and nurtured in pre-service mathematics teacher education. Findings of this study attempt to elucidate how, via mechanisms or infrastructures within student teaching practicum, significant development of habits of mind could be possibly forged among prospective mathematics teachers in order to maximize their student teaching experience and to facilitate them into participating in Lesson Study as they step into the profession